The SAMHD1 rs6029941 (A/G) Polymorphism Seems to Influence the HTLV-1 Proviral Load and IFN-Alpha Levels - Queiroz, Maria Alice Freitas; Amoras, Ednelza da Silva Graça; Moura, Tuane Carolina Ferreira; da Costa, Carlos Araújo; Sousa, Maisa Silva de; Lima, Sandra Souza; Ishak, Ricardo; Vallinoto, Antonio Carlos Rosário (Frontiers in Cellular and Infection Microbiology, 2020)
SAMHD1, a host dNTPase, acts as a retroviral restriction factor by degrading the pool of nucleotides available for the initial reverse transcription of retroviruses, including HTLV-1. Polymorphisms in the SAMDH1 gene may alter the enzymatic expression and influence the course of infection by the virus. The present study investigated the effect of polymorphisms on HTLV-1 infection susceptibility and on progression to disease in 108 individuals infected by HTLV-1 (47 symptomatic and 61 asymptomatic) and 100 individuals in a control group. SAMHD1 rs6029941 (G/A) genotyping and HTLV-1 proviral load measurements were performed using real-time PCR and plasma IFN-α was measured by ELISA. Polymorphism frequency was not associated with HTLV-1 infection susceptibility or with the presence of symptoms. The proviral load was significantly higher in symptomatic individuals with the G allele (p = 0.0143), which presented lower levels of IFN-α (p = 0.0383). SAMHD1 polymorphism is associated with increased proviral load and reduced levels of IFN-α in symptomatic patients, and may be a factor that contributes to the appearance of disease symptoms.